2017
DOI: 10.1016/j.chom.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Global Reprogramming of Host Kinase Signaling in Response to Fungal Infection

Abstract: Summary Cryptococcus neoformans (Cn) is a deadly fungal pathogen whose intracellular lifestyle is important for virulence. Host mechanisms controlling fungal phagocytosis and replication remain obscure. Here, we perform a global phosphoproteomic analysis of the host response to Cryptococcus infection. Our analysis reveals numerous and diverse host proteins that are differentially phosphorylated following fungal ingestion by macrophages, thereby indicating global reprogramming of host kinase signaling. Notably,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 68 publications
(84 reference statements)
2
66
1
Order By: Relevance
“…They are involved in cellular processes ranging from gene regulation, apoptosis, and cytokine release to differentiation and survival of T-lymphocytes and monocyte-derived cells (20,21). Interestingly, a recent study based on phosphoproteomic analysis identified another member of this family, CaMK2, as a protein involved in C. neoformans phagocytosis (22). This work did not yield CaMK2, which may reflect the very distinct approaches of the two studies.…”
Section: Figcontrasting
confidence: 38%
“…They are involved in cellular processes ranging from gene regulation, apoptosis, and cytokine release to differentiation and survival of T-lymphocytes and monocyte-derived cells (20,21). Interestingly, a recent study based on phosphoproteomic analysis identified another member of this family, CaMK2, as a protein involved in C. neoformans phagocytosis (22). This work did not yield CaMK2, which may reflect the very distinct approaches of the two studies.…”
Section: Figcontrasting
confidence: 38%
“…Towards addressing this issue, we reported a functional analysis of host factors that regulate the infection, intracellular replication, and non-lytic release of Cn from host cells (Qin et al, 2011). We extended these findings by performing a phosphoproteomic analysis of the host response to Cn infection (Pandey et al, 2017). This analysis demonstrated that host AIC proteins, and upstream regulatory molecules, contribute to the internalization and intracellular replication of the pathogen in macrophages (Pandey et al, 2017).…”
Section: Introductionmentioning
confidence: 90%
“…We extended these findings by performing a phosphoproteomic analysis of the host response to Cn infection (Pandey et al, 2017). This analysis demonstrated that host AIC proteins, and upstream regulatory molecules, contribute to the internalization and intracellular replication of the pathogen in macrophages (Pandey et al, 2017). This work also raised questions about the cellular and molecular mechanisms by which these proteins contribute to this phenotype.…”
Section: Introductionmentioning
confidence: 90%
“…Discovery‐based proteomics, which relies on the generation of peptides following enzymatic digestion of proteins, is commonly referred to as “bottom‐up proteomics.” This approach enables the unbiased analysis of biological systems, including regulation of cellular processes and protein secretion, as well as communication patterns among cells (Ball, Bermas, Carruthers‐Lay, & Geddes‐McAlister, ; Sukumaran et al., ). In Cryptococcus neoformans , an opportunistic human fungal pathogen, defining changes in protein abundance provides novel insight into the production of virulence factors and the responses of both the host and pathogen to infection (Geddes et al., , ; Pandey et al., ). Moreover, the role of MS‐based proteomics in drug discovery also promotes its application in defining biological processes or targets relevant during the evolution of antifungal resistance (Geddes‐Mcalister & Shapiro, ; Moloney, Owens, & Doyle, ; Pais, Costa, et al., ; Pais, Pires, et al., ).…”
Section: Introductionmentioning
confidence: 99%